2015
DOI: 10.1002/erv.2369
|View full text |Cite
|
Sign up to set email alerts
|

Day Hospital Treatment for Anorexia Nervosa: A 12‐Month Follow‐up Study

Abstract: Day hospitals (DHs) represent a treatment option for anorexia nervosa (AN), a mental disorder that is difficult to treat and has no evidence-based treatments available. We aimed to determine the effectiveness of a DH treatment that was specifically focused on the emotions of severe AN patients. Body mass index and eating psychopathology were the primary outcome measures. Fifty-six adult patients with AN were assessed upon admission, at the end of treatment (EOT) and at a 12-month follow-up evaluation (T18) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 49 publications
4
37
0
3
Order By: Relevance
“…Ten open PHP trials focused primarily on adults (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Goddard et al, ; Jones et al, ; Olmsted et al, ; Olmsted et al, ; Willinge et al, ; Zeeck et al, ) (Table ). All of these studies reported significant improvements in BMI for patients with AN and/or reductions in binge and purge frequency for patients with BN; six of these studies reported medium to large effect sizes (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Willinge et al, ; Zeeck et al, ). For psychological measures, several studies reported significant improvements in measures of depression and anxiety, in addition to the specific measures of ED pathology (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Jones et al, ; Olmsted et al, ; Olmsted et al, ; Willinge et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten open PHP trials focused primarily on adults (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Goddard et al, ; Jones et al, ; Olmsted et al, ; Olmsted et al, ; Willinge et al, ; Zeeck et al, ) (Table ). All of these studies reported significant improvements in BMI for patients with AN and/or reductions in binge and purge frequency for patients with BN; six of these studies reported medium to large effect sizes (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Willinge et al, ; Zeeck et al, ). For psychological measures, several studies reported significant improvements in measures of depression and anxiety, in addition to the specific measures of ED pathology (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Jones et al, ; Olmsted et al, ; Olmsted et al, ; Willinge et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…All of these studies reported significant improvements in BMI for patients with AN and/or reductions in binge and purge frequency for patients with BN; six of these studies reported medium to large effect sizes (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Willinge et al, ; Zeeck et al, ). For psychological measures, several studies reported significant improvements in measures of depression and anxiety, in addition to the specific measures of ED pathology (Abbate‐Daga et al, ; Crino & Djokvucic, ; Exterkate et al, ; Fittig et al, ; Jones et al, ; Olmsted et al, ; Olmsted et al, ; Willinge et al, ). Zeeck et al () provided additional support for PHP treatment for BN by matching a PHP sample to an extended inpatient sample; no significant differences between the two modalities in treating patients were reported, as measured by the Eating Disorder Inventory (EDI).…”
Section: Resultsmentioning
confidence: 99%
“…Foram encontradas também intervenções com medicamentos como a fluoxetina (Sørensen et al, 2011), sozinhos ou combinados com psicoterapia psicodinâmica (Koppers et al, 2011); e também intervenções combinadas com outros tratamentos multidisciplinares, tais como dieta alimentar e acompanhamento familiar (Abba-te Daga et al, 2015).…”
Section: Modalidades De Psicoterapiaunclassified
“…Outro método utilizado para complementar os questionários foram entrevistas presenciais semiestruturadas desenvolvidas para o próprio estudo, ou entrevistas estruturadas, por exemplo: Operationalized Psychodynamic Diagnosis -OPD Task Force (Levi et al,2015;Vinnars et al, 2009;Marttunen et al, 2008;Johansson et al, 2013;Kronström et al, 2009;Koppers et al, 2011;Høglend et al, 2008;Gude e Hoffart, 2008;Abbate-Daga et al, 2015;Berghout e Zevalkink, 2009;Lilliengren et al, 2015;Grande et al, 2009;Arvidson et al, 2011;Leichsenring et al, 2014). O estudo que avaliou custo-efetividade dos serviços de saúde também utilizou, além dos questionários, os registros nacionais de verificação para compor as medidas de follow-up (Abass et al, 2015).…”
Section: Métodos E Medidas Utilizados No Follow-upunclassified
See 1 more Smart Citation